2022
DOI: 10.21037/gs-21-877
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management and prognosis of phyllodes tumors of the breast

Abstract: Background: Regardless of histological grade, phyllodes tumors (PTs) exhibit the potential of local recurrence. The National Comprehensive Cancer Network (NCCN) recommends wide local excision (WLE) with a 1 cm margin or more for borderline/malignant PTs but excisional biopsy for benign PTs. However, the treatment of benign PTs remains controversial and the clinicopathologic risk factors for the local recurrence is still unclear. Methods: We retrospectively analyzed 238 patients with PTs who underwent surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Three studies (Chao et al., 2020, Vargas et al., 2006, and Ji et al., 2022) ( 11 , 12 , 19 ) did not present the Breast Imaging-Reporting and Data System (BI-RADS) classification of the lesions. Ouyang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (Chao et al., 2020, Vargas et al., 2006, and Ji et al., 2022) ( 11 , 12 , 19 ) did not present the Breast Imaging-Reporting and Data System (BI-RADS) classification of the lesions. Ouyang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown significant heterogeneity in margin management. Although older studies have recommended resection of tumors with wide margins [ 34 36 ], contemporary studies recommend a wait-and-watch approach [ 22 , 30 , 31 , 37 ]. In some studies, re-surgery in tumors with positive margins has been reported to have no effect on recurrence [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria, 342 patients were included in the analytic cohort. Among these, 238 patients were reported in our previous study (17). Only patients who underwent surgery in our hospital and were pathologically confirmed as PT were included.…”
Section: Patient Population and Data Collectionmentioning
confidence: 99%